ANALISIS HUKUM HAK MEMILIH PENYANDANG DISABILITAS MENTAL DALAM PEMILIHAN UMUM: Analisis Hukum Hak Memilih Penyandang Disabilitas Mental Dalam Pemilihan Umum - Adhyaksa, Andika (Mendapo: Journal of Administrative Law, 2023)
This study aims to analyze the legal position of the right to vote for people with disabilities in general elections and to analyze the validity of the right to vote for people with mental disabilities in elections. The type of research used is the normative legal research type, which lays down the law as a system of norms. Techniques for obtaining legal materials by means of library research by collecting legal materials carried out by reading, quoting, recording and understanding various legal literature and legislation. The legal material analyzed is in the form of laws and regulations and legal issues which are then interpreted using deductive thinking. The results showed that 1) Persons with Mental Disabilities are citizens who are recognized and upheld the right to be able to vote and be elected in General Elections as mandated by the constitution to provide equal position of the community in law and government and has been guaranteed in laws and regulations. 2) The fulfillment of the rights of persons with mental disabilities is still widely rejected by the public and is contrary to the holding of elections based on the principles of direct, general, free, secret, honest and fair.